قدیم تہذیبوں میں عرف و عادت کا تصور اور عہدِ نبوی ﷺ میں اس کی فقہی حیثیت: تحقیقی و تقابلی جائزہ: The Concept of Custom in Ancient Civilizations and Its Jurisprudential Status in the Prophetic Era: An Analytical and Comparative Study (Al-Aasar, 2025)
The study explores the concept of custom and tradition in ancient civilizations and examines its jurisprudential status during the Prophetic era in Islam. In pre-Islamic societies such as Arabia, Persia, Rome, India, and Mesopotamia, customs functioned as unwritten laws regulating family life, trade, dispute resolution, and social order. These customs embodied collective experiences, cultural values, and societal needs, often transmitted orally through generations. With the advent of Islam, the Prophet Muhammad ﷺ encountered a society governed by strong tribal customs. Instead of rejecting all existing customs or adopting them uncritically, he evaluated them against the principles of divine revelation. Customs that promoted justice, equality, hospitality, fulfillment of covenants, and kinship ties were endorsed, while practices based on oppression, tribal arrogance, exploitation, and immorality were abolished. This pragmatic yet principled approach integrated beneficial customs into the Islamic legal framework. During the Prophetic era, and later in the period of the Rightly Guided Caliphs, customs played a role in issues such as contracts, marriage, dowry, reconciliation, and compensation, provided they did not contradict the Qur’an and Sunnah. This methodology highlights the flexibility and universality of Islamic law, which harmonizes divine guidance with human experience to address social realities. By recognizing custom as a secondary but vital source of jurisprudence, Islamic law established itself as a dynamic, adaptable, and human-centered system. Thus, the concept of custom demonstrates how Islamic jurisprudence combines eternal principles with contextual realities, ensuring relevance across time and cultures.